WADAH KOMUNITAS GOTONG ROYONG CBS - Bryan Marco Wijaya; Petrus Rudi Kasimun (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
The project, which is located in Cipinang Besar Selatan (CBS) sub-district, has become a prototype of the CBS community's daily life. "Community" and "mutual cooperation" are the basic essences held by the local society and these essences can be clearly seen from the existing conditions in the CBS village. They work together to build positive activities in their village such as; The First Smoke-Free Village in Jakarta, "Kampung Warna Warni", "Kampung Listrik Indie". However, these activities were formed unevenly in the CBS village. This problem is tried to be resolved through a design that has been proposed. The design is about how the CBS Mutual Cooperation Community could become a Third Place that is not only a place to carry out routines and activities. It also can become an entertainment facility and education for the CBS community. As a result, the CBS community could grow forward and develop together. The program is arranged in accordance to the daily activities of the CBS community. Therefore, the CBS Mutual Cooperation Community may become a center for the village activities that has been separated from each other. The society will not only be participating in the program, but they are involved in its development, like assembling the main material in the design of Glulam Timber with a modular system, up to the management stage. As well as the other aspects, it can be said that the CBS Gotong Royong Community Forum not only answer the essence of "community" and "mutual cooperation", but also answers the challenges of the Third Place itself. Keywords:  Cipinang besar selatan; community; mutual cooperationAbstrakProyek yang berlokasi di Kelurahan Cipinang Besar Selatan (CBS) ini menjadi sebuah prototype bagi kehidupan sehari-hari dari masyarakat perkampungan CBS, dimana “komunitas” dan “gotong royong” adalah esensi dasar yang dipegang teguh oleh masyarakat sekitar. Esensi dari “komunitas” dan “gotong royong” dapat secara nyata dilihat apabila melihat kondisi existing pada perkampungan CBS, dimana mereka bergotong-royong membangun kegiatan-kegiatan positif pada kampung mereka seperti; Kampung Bebas Asap Rokok Pertama di Jakarta, Kampung Warna Warni, Kampung Listrik Indie. Namun kegiatan-kegiatan positif terbentuk secara tidak merata pada perkampungan CBS. Hal itulah yang berusaha diselesaikan dalam desain yakni tentang bagaimana Wadah Komunitas Gotong Royong CBS dapat menjadi sebuah Third Place yang bukan saja hanya menjadi wadah untuk melakukan rutinitas dan aktivitas, tetapi menjadi sarana hiburan dan juga edukasi bagi masyarakat CBS, sehingga perkampungan CBS dapat tumbuh maju dan berkembang bersama-sama. Program yang diusung pun sesuai dengan aktivitas sehari-hari masyarakat CBS, sehingga Wadah Komunitas Gotong Royong CBS bukan hanya sebuah wadah, namun menjadi pusat bagi aktivitas-aktivitas perkampungan CBS yang selama ini terpisah satu dengan lainnya. Masyarakat pun bukan hanya menjadi pengguna program, namun mereka dilibatkan sejak awal pembangunan seperti halnya perakitan material utama pada desain yakni Glulam Timber dengan sistem modular, hingga dengan tahap pengelolaan. Begitu juga dengan beberapa aspek lainnya, sehingga dapat dikatakan Wadah Komunitas Gotong Royong CBS bukan saja hanya dapat menjawab esensi dari “komunitas” dan “gotong royong”, namun juga menjawab tantangan dari Third Place itu sendiri.